The old curiosity shop - Dickens, Charles, 1812-1870.; Cattermole, George, 1800-1868; Wicklow, William Howard, Earl of, 1788-1869. (Oxford : Oxford University Press, 1951)
The Victorian tale of Little Nell, a girl who is uprooted from her secure and innocent childhood and cast into a world of evil when she and her grandfather are pursued relentlessly through England by the evil and loathsome dwarf Quilp.
Young Adult
Keywords: Gambling -- England -- Fiction; Good and evil -- Fiction; Grandparent and child -- Fiction; Gambling -- Fiction; Good and evil -- Fiction; Grandparent-grandchild relationship -- Fiction; England -- Social life and customs -- 19th century -- Fiction; England -- Social life and customs -- 1800-1899 (19th century) -- Fiction; Didactic fiction